2020
DOI: 10.3389/fpls.2020.00394
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Systems Biology and Synthetic Biology in Relation to Drought Tolerance or Avoidance in Plants

Abstract: Drought stress has been a long-time limitation to crop production that is being exacerbated by climate change and associated reductions in the availability of blue water resources for agriculture. Most existing food and industrial crops are susceptible to drought stress, which can cause a significant loss in crop yield. Therefore, our ability to develop more climate-resilient crops that are more heat and drought tolerant will become increasingly important in the near future. In nature, plants have evolved two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…They avoid drought with a reversed day/night stomatal movement compared to C3 or C4 photosynthesis plants and provide high water‐use efficiency (WUE) (Yang et al, 2015). The drought experienced in crop plants is mostly seasonal (Yang et al, 2020). In nature, facultative CAM plants can be induced by CAM photosynthesis when exposed to drought stress (Yang et al, 2019).…”
Section: Crassulacean Acid Metabolism (Cam)‐related Genes and Genetic Engineering Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…They avoid drought with a reversed day/night stomatal movement compared to C3 or C4 photosynthesis plants and provide high water‐use efficiency (WUE) (Yang et al, 2015). The drought experienced in crop plants is mostly seasonal (Yang et al, 2020). In nature, facultative CAM plants can be induced by CAM photosynthesis when exposed to drought stress (Yang et al, 2019).…”
Section: Crassulacean Acid Metabolism (Cam)‐related Genes and Genetic Engineering Approachesmentioning
confidence: 99%
“…Similarly, over‐expression of a drought‐sensitive NAC family gene from Kalanchoe fedtschenkoi (KfNAC83) has revealed an increased resistance to water stress in A thaliana . It has also been shown that overexpression of the rice gene OsNAR2.1 , which encodes a nitrate transporter partner protein, has increased the drought tolerance in rice (Yang et al, 2020).…”
Section: Crassulacean Acid Metabolism (Cam)‐related Genes and Genetic Engineering Approachesmentioning
confidence: 99%
“…CAM engineering requires design of multiple gene modules involved in carboxylation, decarboxylation, and stomatal movement, as well as genes involved in leaf succulence and vacuole size [233][234][235]. Biosystems design approaches could be used to integrate these CAM-related gene modules into plants, preferably using gene circuits to establish drought-inducible CAM (or CAM-on-demand) systems [236].…”
Section: Plant Biosystems Design For Increasing Plant Stressmentioning
confidence: 99%
“…biology technologies [17,18]. Synthetic techniques for regulating gene expression and cellular processes, particularly chemically inducible systems, CRISPR/Cas9-based technologies, and other advancements in genome engineering, are critical for advancing plant synthetic biology in the future [12,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%